Space arrangement of service areas and furnishings of selected public libraries in Metro Manila - Elizes, Zyril D. (1999)
This study is an investigation of the space arrangement of service areas and furnishings of the seven selected public libraries in Metro Manila (Caloocan City Library, Makati City Library, Malabon Public Library, Mandaluyong City Library, Marikina City Library, Pasig City Library and Museum, and Quezon City Library). the specific objectives of the study are: 1) to identify the furnishings that are presently used in the selected public libraries; 2) to ascertain the functional service areas in the selected public libraries; 3) to determine the total space assigned for each service areas; 4) to know if these libraries follow standards for space arrangement of service areas and furnishings; and 5) know the perception of the users regarding the matter.